Análisis económico-financiero en el engorde de cuyes utilizando tres tipos de forraje verde hidropónico (cebada, avena y maíz) en la comunidad Tamboloma de la parroquia Pilahuin cantón Ambato - Ángel Damián, Punina Agualongo (2015)
The main objective of the research project was to make the ECONOMIC AND FINANCIAL ANALYSIS IN GUINEA PIG FARMING USING THREE TYPES OF GREEN FODDER HYDROPONICS (BARLEY, OATS AND CORN) Tamboloma IN THE PARISH COMMUNITY AMBATO Pilahuín CANTON, which suggest assess which of hydroponic sprouts is the most effective in the guinea pig fattening process, compare the profitability on the financial analysis of the use of sprouted applying the cost-benefit ratio as a function of each of the treatments used, then participate with members of the community the results of the project through a field day. The study sample was 72 guinea pigs, 36 males and 36 females, divided into three treatments with three replicates located inside a shed of 50 square meters. All treatments had the same driving conditions, considering that worked with individuals females half and half machos. Los results obtained were as follows: Best Hydroponic Green Forage consumption (FVH) was higher in the treatment two (Avena balanced 60% + 40%) for both males and females, being due to the high palatability was observed throughout the trial, the opposite case in consumption was for males and females of treatment three (Corn 60% + 40% balanced ) . The largest single weight increase was for the male and female guinea pigs treatments two (Avena balanced 60% + 40%) and the control (60% + balanced Alfalfa 40%), with a weight increase of 629.32 gr. and 545.41 g for males and females respectively. Finally found the three treatment (60% + balanced Corn 40%) that provided a weight of 609.42gr. and 528.16gr. for males and females 5 respectivamente. La higher feed conversion was achieved in treating three (60% + Corn balanced 40%) for males and females, in the first case with 2.53 gr. and 2.20gr. respectively to convert one gram of mass muscular. Los male and female guinea pigs treatment two had the greater weight gain and improved feed conversion .The greatest performance was achieved in Treatment $ 2.09 for one guinea pig. The observed mortality was zero% in the experimental group. Results and conclusions periten treatment I recommend hydroponic forage oat based and balanced.